Программа курса лекций "Качественные методы социологических исследований" - Сусак, В.; Середа, В. (Социология: теория, методы, маркетинг, 2001)
Topic 1. Qualitative methods in sociological studies.Topic 2. "Qualitative" and "quantitative" sociological studies.Topic 3. Biographical studies: life history, sociology of personality, sociology of life.Topic 4. Family communities and social mobility.Topic 5. Topic studies (case studies): case studies, deviation researches.Topic 6. Gender studies: "female" and "male" problems.Topic 7. Social changes.Topic 8. Sociology of city and country.Topic 9. Marketing and industrial sociology.Topic 10. Historical studies (oral history).Topic 11. Ethnographical and ethnological researches.Topic 12. General methodology of research projects in the "qualitative" sociology system.